Analisis Semiotik Puisi Akulah Medan Karya Teja Purnama - Rahmadani, Novia; Ramadan, Gilang; Isman, Muhammad (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study analyzes semiotic signs in Teja Purnama's poem "Akulah Medan" using Charles Sanders Peirce's theory, which includes icons, indices, and symbols. The semiotic approach was chosen because the poem represents the historical, social, and cultural significance of the city of Medan. The method used is qualitative descriptive, using reading, listening, and note-taking techniques. The analysis shows that the poem "Akulah Medan" depicts Medan as a symbol of love, identity, and social criticism.